2015 IEEE MTT-S International Microwave Symposium 2015
DOI: 10.1109/mwsym.2015.7166789
|View full text |Cite
|
Sign up to set email alerts
|

New approach for an accurate Schottky Barrier Height's extraction by I-V-T measurements

Abstract: This paper proposes a diagnostic tool dedicated to the analysis of the Schottky Barrier Height (SBH). The proposed method is mainly relevant for studying gate related failure mechanisms in electronic devices. In this case, the SBH of gallium nitride High Electron Mobility Transistors (HEMTs) is investigated in terms of mean SBH's value and dispersion. It is shown that according to given temperature and gate current ranges, linear relationships can be extracted between the mean SBH and the inhomogeneities that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…From [5], the determination of the mean SBH and a related dispersion ( , ) is found not to be sufficient to get the Schottky Barrier Height determined accurately. By varying the IGS current range (considering a 2-decades window) or by changing the temperature, it is demonstrated that:…”
Section: Extraction Of the Mean Sbh And Dispersionextracting The Accumentioning
confidence: 95%
See 3 more Smart Citations
“…From [5], the determination of the mean SBH and a related dispersion ( , ) is found not to be sufficient to get the Schottky Barrier Height determined accurately. By varying the IGS current range (considering a 2-decades window) or by changing the temperature, it is demonstrated that:…”
Section: Extraction Of the Mean Sbh And Dispersionextracting The Accumentioning
confidence: 95%
“…Since we are talking about diodes and non-destructive techniques, the most common approach consists in the analysis of the SBH. This part of the work is based on prior studies [4] [5], which present an accurate tool for extracting the SBH alone, through the quantification of the defects impact on the global SBH. The technique from [5] brings information about a mean SBH and its relative dispersion (inhomogeneity of the barrier, Fig.…”
Section: Electrical Measurements and Modelling Of The Gate Schottky Dmentioning
confidence: 99%
See 2 more Smart Citations
“…The induced degradation during HTRB stress impacts the 1/f noise source (electron carrier fluctuation in the leakage conduction path), and thus the leakage current IG can be used as a dependable marker of reliability for device selection. A unified model has been developed to account for the gate Schottky barrier height inhomogeneity [28], for the thermal evolution of the IG-VGS plots and for the trap effects on the transient characteristics IGS(time) and IDS(time) [29]. In addition to these electrical and noise characterizations, TCAD models have been developed to successfully account for the physical origin of the evolutions on drain current and gate leakage current [30,31].…”
Section: Electrical and Lfn Measurements And Models For Reliability Cmentioning
confidence: 99%